(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This work outlines the professional life of Dr. Ponciano Tenorio Montes (1912- 1963), who was the first medic with studies in psychiatrics to practice in the state of Michoacan. Also discussed are the historic antecedents and the circumstances that led to the foundation in Morelia in the Medical Faculty of the first department of neuron-psychiatrics (1950-1952) in the country, along with the first mental hospital in Michoacan in 1958. He was also the Regent of the First and National College of the University of Michoacan, delegate at the Fourth International Congress of Mental Health in Mexico City (in December 1951) and also at the first formal reunion of the Psychiatric Association of Latin America (APAL) in Jalapa. He is considered one of the most prominent medical doctors of his time, and because of this the understanding of his work contributes to the understanding of the immediate past of medicine in Michoacan.